2023
DOI: 10.25122/jml-2023-0148
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarkers to predict hemorrhagic transformation and ischemic stroke outcomes in a prospective cohort study

Elena Costru-Tasnic,
Mihail Gavriliuc,
Elena Manole

Abstract: Ischemic stroke (IS) remains one of the most frequent causes of death and disability worldwide. Identifying possible prognosis factors for IS outcomes, including hemorrhagic transformation (HT), could improve patients' recovery. This study aimed to investigate the potential prognosis role of non-specific laboratory data at admission and baseline MMP-2 and MMP-9 serum levels in predicting HT risk, discharge, and 3-month follow-up status of IS patients. Data from 150 successive acute cerebral infarction patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The data from the literature are contradictory in this regard. In a prospective cohort study of 150 patients with AIS, 55 experienced HT, but diabetes was not found to be a risk factor for HT [15]. In contrast, other studies found that diabetes mellitus is a risk factor for the development of HT [16][17][18].…”
Section: Discussionmentioning
confidence: 87%
“…The data from the literature are contradictory in this regard. In a prospective cohort study of 150 patients with AIS, 55 experienced HT, but diabetes was not found to be a risk factor for HT [15]. In contrast, other studies found that diabetes mellitus is a risk factor for the development of HT [16][17][18].…”
Section: Discussionmentioning
confidence: 87%
“…In ex vivo studies, endothelial cells exposed to prolonged hyperglycemic conditions showed elevated MMP-9 activity, which could be ameliorated by free radical scavengers [ 23 , 24 ]. Moreover, elevated MMP-9 levels have been associated with hemorrhagic conversion after r-tPA or mechanical thrombectomy treatment in stroke patients [ 25 , 26 , 27 ]. Thus, in AIS patients with poorly controlled diabetes, their increased risk of symptomatic hemorrhagic transformation might be explained in part by increased MMP-9 activity, though further studies are needed to confirm this hypothesis and understand its relationships with the time course and mechanisms of effect.…”
Section: Discussionmentioning
confidence: 99%